Further Studies on Thrombin-Coagulase - Soulier, J. P; Prou, O; Hallé, L (Thrombosis and Haemostasis, 1970)
A kinetic study of the interaction between prothrombin and staphylocoagulase shows that the thrombic activity which forms (thrombin-coagulase) is the result of a molecular complex in which the active site of prothrombin is exposed but other sites necessary for adsorption or inhibitors action are masked. The high speed of the activation, the independence from the temperature, and the fact that the yield of thrombin activity is directly related to the amount of each of the two reagents are the main arguments against an enzymatic splitting of prothrombin by staphylocoagulase. Some further properties of thrombin-coagulase complex are studied.